2017
DOI: 10.1002/jctb.5462
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of glycerol to 1,2‐propanediol in a continuous flow trickle bed reactor

Abstract: BACKGROUND Hydrogenolysis of glycerol to glycols in continuous flow three phase reactors is of practical importance due to the need to give value to huge amounts of surplus glycerol. Thermodynamic and kinetic aspects must be revised for a proper design. The system was studied in a trickle‐bed reactor using copper chromite and Cu/Al2O3 as catalysts. RESULTS Phase equilibrium and flow pattern were verified. Solid, liquid and gas phases were present, with the liquid phase in ‘trickling’ flow. Catalysts were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…A large number of surplus glycerol processing methods have already been proposed such as hydrogenolysis to 1,2-propanediol [3], dehydration to acrolein [4,5], oxydehydration to acrylic acid [6], chlorination to epichlorohydrin [7], carbonation to glycerol carbonate [8]. One of the most promising chemicals, which can be obtained from glycerol, is lactic acid known as 2-hydroxypropanoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of surplus glycerol processing methods have already been proposed such as hydrogenolysis to 1,2-propanediol [3], dehydration to acrolein [4,5], oxydehydration to acrylic acid [6], chlorination to epichlorohydrin [7], carbonation to glycerol carbonate [8]. One of the most promising chemicals, which can be obtained from glycerol, is lactic acid known as 2-hydroxypropanoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Copper chromite and Cu/Al 2 O 3 catalysts had very different physical and chemical properties; however, in the hydrogenolysis of GL, carried out in a trickle-bed reactor, 97 % selectivity of 1,2-PD and complete conversion of GL were obtained for both catalysts at 503 K and 14 bar H 2 . [174] This comparable activity would be related to the presence of Cu 0 species in both catalysts, as seen by XPS. The authors observed also that higher temperatures produced a decrease in the selectivity to 1,2-PD due to the formation of different by-products: minor alcohols in presence of Cu/Al 2 O 3 , and HAc and 3-HPA in the case of copper chromite.…”
Section: Coppermentioning
confidence: 79%
“…Copper chromite and Cu/Al 2 O 3 catalysts had very different physical and chemical properties; however, in the hydrogenolysis of GL, carried out in a trickle‐bed reactor, 97 % selectivity of 1,2‐PD and complete conversion of GL were obtained for both catalysts at 503 K and 14 bar H 2 [174] . This comparable activity would be related to the presence of Cu 0 species in both catalysts, as seen by XPS.…”
Section: Late Transition Metalsmentioning
confidence: 92%
See 2 more Smart Citations